2013
DOI: 10.2136/sssaj2012.0221
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Impacts of Crop Residue Removal and Tillage on Soil Organic Matter Maintenance

Abstract: Cellulosic biofuel production may generate new markets and revenue for farmers. However, residue removal may cause environmental problems such as soil erosion and soil organic matter (SOM) loss. The objective of this study was to determine the amounts of residue necessary for SOM maintenance under different tillage and residue removal scenarios for corn–soybean [Zea mays L.–Glycine max (L.) Merr.] and continuous corn rotations for a site in west‐central Minnesota. We employed a process‐based model (CQESTR) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
4
16
0
2
Order By: Relevance
“…A number of studies have reported good agreement between CQESTR simulated SOC and measured SOC (Liang et al, 2008(Liang et al, , 2009Gollany et al, 2010Gollany et al, , 2011Dalzell et al, 2013;Wienhold et al, 2016). Liang et al (2009) used data from 13 experiments ranging from 20 to >100 yr in duration to validate CQESTR and found that the largest percentage of MSD was due to lack of correlation (scatter) for 10 of the sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported good agreement between CQESTR simulated SOC and measured SOC (Liang et al, 2008(Liang et al, , 2009Gollany et al, 2010Gollany et al, , 2011Dalzell et al, 2013;Wienhold et al, 2016). Liang et al (2009) used data from 13 experiments ranging from 20 to >100 yr in duration to validate CQESTR and found that the largest percentage of MSD was due to lack of correlation (scatter) for 10 of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…A 20‐yr simulation period was used, and model output for Years 3 and 15 were used to simulate management effects on SOC content over a time period similar to 1999 to 2011. The 3‐yr spin‐up period allowed the model to establish SOC pools and avoided model artifacts (Álvaro‐Fuentes et al, 2009; Dalzell et al, 2013). Model output and measured SOC were regressed, and the mean squared deviation (MSD) was decomposed into nonunity slope, squared bias, and lack of correlation components (Gauch et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Todos los suelos, independientes de su manejo, presentan valores más altos de materia orgánica en las muestra de 0-10 cm de profundidad, que de 10-20 cm, lo cual coincide con lo expuesto por Mikha y Rice (2004). Estas diferencias a distintas profundidades fueron observadas también por otros autores (Six et al, 2000;Apezteguía y Sereno 2002;Moore y Turunen, 2004;Dalzell et al, 2013), concluyendo que la cantidad de MOS disminuye en profundidad dentro del perfil. Para el caso del SVA pradera, el porcentaje de MOS encontrado es mayor, en ambas profundidades, que el SVC pradera.…”
Section: Evaluación Del Contenido De Materia Orgánica Con El Historiaunclassified
“…Studies have shown that SOM content is directly related to the amount of residue applied to the soil (Rasmussen et al, 1980;Robinson et al, 1996;Dalzell et al, 2013;Kludze et al, 2013). Barber (1979) showed that above ground biomass removal (BR) negatively affects SOM levels.…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in SOM can however be fully or partially mitigated with appropriate management such as reduced tillage, improved crop nutrition, organic amendments, cover crops and perennial vegetation (Janzen et al, 1998;Bruce et al, 1999;Dalzell et al, 2013;Zhao et al, 2013). Several studies have evaluated SOM content change as a function of different tillage and cropping systems (Mahboubi et al, 1993;Reicosky et al, 1995;Hunt, 1996;Rasmussen et al, 1998;Deen and Kataki, 2003), crop management (Halvorson et al, 2002;McConkey et al, 2003) with cover crops and legumes (Drinkwater et al, 1998;Fortuna et al, 2003), mineral fertiliser application (Halvorson et al, 1999;Russell et al, 2005), farmyard and green manure application (Sommerfeldt et al, 1988;Nardi et al, 2004;Sisti et al, 2004) and residue management (Rasmussen et al, 1980;Bohm et al, 2002).…”
Section: Introductionmentioning
confidence: 99%